Design de um aplicativo para gestão participativa no contexto escolar - Pinto, Gilian de Moraes (2024)
The aim of this study was to assess how the use of technology can contribute to collective participation in the construction of the Pedagogical Political Project and in decision-making at the Polytechnic College of the Federal University of Santa Maria. The study looked at the tools and forms of participation provided by the management so that the institution's school community can participate and contribute to more participatory management. Interviews were conducted with representatives of the school community, including managers, teachers, administrative staff, students and family members, as well as documentary research to analyze the guidelines and forms of participation at the institution. The study used a qualitative approach, investigating the meanings and perceptions of human relations in a subjective way about the activities that involve the school environment surveyed, which sought to understand the perception of those involved in relation to their participation. Following the information collected, it was found that the participation of the school community in decision-making and in the construction of the Pedagogical Political Project takes place at specific times and usually in person, making it impossible for many members of the school community to take part. The analysis of the data revealed the main demands and the form of participation that will facilitate the participation of the school community surveyed. Finally, the work presents the design of a smartphone application to help the institution promote participatory management, thereby increasing the participation of the school community, promoting a culture of participation in the institution and having a positive impact on the collective decisions of the Polytechnic College.